Brushstrokes of Tomorrow: Exploring the Art of AI - Tanish M Sanghvi; Ricky; Shivani Rajkumar; Tirishaant Kartik; Sonia Maria D’Souza (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In recent years, the advancement of Artificial Intelligence (AI) technology, particularly in deep learning algorithms like Generative Adversarial Networks (GANs) and Variational Autoencoders (VAE), has led to significant developments in AI-based art generation across various sectors within the art industry. The year 2022 witnessed an explosion of AI-generated art, particularly in creative design, resulting in the production of numerous outstanding works that have enhanced the efficiency of art design processes. This study delves into the application and design characteristics of AI generation technology within two specific sub-fields: AI painting and AI animation production. A comparative analysis between traditional painting methods and AI-generated painting techniques is conducted to discern differences. Through this research, the paper synthesizes the advantages and challenges inherent in the AI creative design process. Despite technical limitations and issues such as copyright and income distribution, AI art designs demonstrate promise in facilitating artistic innovation and technological integration within the art domain. Their potential for advancing sub divisional artistic practices and their intersection with technology renders them highly valuable subjects for further research and exploration.
Keywords: AI based art generation; AI deep learning; Generative Adversarial Networks; Variational Autoencoders; Art Generation; Creative Designing